2015
DOI: 10.1128/aac.00409-15
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Study Reveals Lack of Pharmacokinetic/Pharmacodynamic Target Attainment in De-escalated Antibiotic Therapy in Critically Ill Patients

Abstract: f De-escalation of empirical antibiotic therapy is often included in antimicrobial stewardship programs in critically ill patients, but differences in target attainment when antibiotics are switched are rarely considered. The primary objective of this study was to compare the fractional target attainments of contemporary dosing of empirical broad-spectrum ␤-lactam antibiotics and narrower-spectrum antibiotics for a number pathogens for which de-escalation may be considered. The secondary objective was to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Recently, De Bus [ 48 ] et al analyzed the effect of de-escalation in 478 anti-pseudomonal antibiotic prescriptions and could not find lower rates of resistant organisms after exposure to anti-pseudomonal beta-lactam antibiotics. Interestingly, Carlier et al [ 49 ] conducted a simulation study showing that the probability of achieving a PK/PD target was lower in the narrower-spectrum antibiotic group (amoxicillin–clavulanic acid, cefuroxime, flucloxacillin, cefazolin and cefepime) using conventional dosing as compared to broad-spectrum antibiotics like meropenem and piperacillin/tazobactam.…”
Section: Antibiotic Stewardship (Ams) and Infection Control Strategiementioning
confidence: 99%
“…Recently, De Bus [ 48 ] et al analyzed the effect of de-escalation in 478 anti-pseudomonal antibiotic prescriptions and could not find lower rates of resistant organisms after exposure to anti-pseudomonal beta-lactam antibiotics. Interestingly, Carlier et al [ 49 ] conducted a simulation study showing that the probability of achieving a PK/PD target was lower in the narrower-spectrum antibiotic group (amoxicillin–clavulanic acid, cefuroxime, flucloxacillin, cefazolin and cefepime) using conventional dosing as compared to broad-spectrum antibiotics like meropenem and piperacillin/tazobactam.…”
Section: Antibiotic Stewardship (Ams) and Infection Control Strategiementioning
confidence: 99%
“… 7 , 8 However, data on target attainment of unbound flucloxacillin in plasma are scarce. Simulation studies based on a small number of patients with MSSA-BSI have demonstrated flucloxacillin underdosing 9 , 10 and high variability of the unbound flucloxacillin fraction, particularly in critically ill patients. 5 , 11 In these studies, the MSSA oxacillin standard epidemiological cut-off value (ECOFF; 2 mg/L) and not the strain-specific flucloxacillin MIC value was used to calculate target attainment.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, in a subgroup analysis, we found no correlation between carbapenem discontinuation and the emergence of CRAB or CRPA (Table S1 in the online supplement file). Carlier and colleagues reported that the probability of reaching the targeted pharmacokinetics (PK) and pharmacodynamics (PD) of narrow-spectrum antibiotics was less than that of broad-spectrum agents [29]. Although a longer duration of therapy would contribute to an increased risk of MDR pathogen emergence, not reaching the PK or PD target could indicate that insufficient drug was administered to obtain a therapeutic response.…”
Section: Discussionmentioning
confidence: 99%